The protective role of single bulb garlic (Allium sativum L.) towards foam cells and vascular cell adhesion molecules-1 (VCAM-1) on mice (Mus musculus) with high-fat diet - Chasanah, Isfatun; Ghofur, Abdul; Lestari, Sri Rahayu (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2019)
Atherosclerosis is initiated by inflammatory response characterized by the accumulation of lipids in the arteries, causing blockage of blood vessels. The excessive of low-density lipoprotein (LDL) in the blood is a major factor in endothelial dysfunction and results in an inflammatory process. The inflammatory process in atherosclerosis is due to the expression of adhesion molecules, vascular cell adhesion molecules-1 (VCAM-1). This research aimed to evaluate the effect of single bulb garlic oil extract (SGBOE) against VCAM-1 expression in high-fat diet mice. Thirty male mice strain Balb/C were acclimatized for one week. Mice were divided into 6 groups (n=5): normal, high-fat diet (HFD), HFD + simvastatin, and HFD + SBGOE 12.5, 25, and 50 mg/kg BW respectively. HFD was given for 45 days. The SGBOE was given for four weeks orally. The aortic VCAM-1 expression was assayed using the immunohistochemical-flouresencemethod. The result of One-Way ANOVA showed that the treatment influenced significantly (p<0.05). The foam cells increase in the high-fat diet group compared than normal mice. Dose 12,5 mg/kg BW reduces VCAM-1 expression near the normal group. Allicin and S-allyl cysteine (SAC) compounds in single bulb garlic are antioxidant compounds that act to prevent oxidative stress and prevention mechanisms against lipoprotein modification.